Peningkatan Literasi Lingkungan Peserta Didik melalui Proyek Bioplastik Rumput Laut Berbasis Environmental-STREAM - Imam Ismawan; Tri Wahyu Agustina; Maratus Solikha (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This research aimed to analyze the improvement of students' environmental literacy through project-based learning combined with the Environmental-STREAM approach by engaging in activities to create bioplastics made from seaweed. The method used was a quasi-experimental method with a Pretest-Posttest Control Group Design. The research sample consisted of 33 tenth-grade high school students divided into an experimental class (n=17) and a control class (n=16). The experimental class received Project-Based Learning (PjBL) integrated with Environmental-STREAM, while the control class received conventional PjBL. Data were collected using an environmental literacy test instrument that includes aspects of knowledge, cognitive skills, attitudes, and behavior. Data analysis was conducted using N-Gain, normality test, homogeneity test, and Mann-Whitney test. The results showed that the experimental class obtained an N-Gain value of 0.75 (high category), while the control class obtained 0.48 (medium category); the knowledge aspect showed the highest improvement with an N-Gain value of 0.81, while the cognitive skills aspect showed the lowest value of 0.61. The Mann-Whitney test results indicated a significance value of 0.004 (p < 0.05), which shows a significant difference in the improvement of environmental literacy between the experimental class and the control class. In conclusion, project-based learning integrated with Environmental-STREAM through the production of seaweed bioplastics is capable of enhancing students' environmental literacy. Keywords: Environmental Change, Environmental Literacy, Environmental-STREAM, Project-Based Learning, Seaweed Bioplastics